Autogenic Training Improves the Subjective Perception of Physical and Psychological Health and of Interpersonal Relational Abilities: An Electronic Field Survey During the COVID-19 Crisis in Spain - de Rivera, Luis; Ozamiz-Etxebarria, Naiara; Dosil-Santamaría, María; de Rivera-Monterrey, Leonor (Frontiers in Psychology, 2021)
Currently, humanity is facing one of the most critical situations of this century, the COVID-19. The adverse effects of the pandemic on the mental health of the population are well known. Fear of illness, confinement, lack of financial resources, or poor social support can influence people’s mental state. Despite these risks, several psychological resources may help address this situation. The present study investigated the effectiveness of a self-relaxation techniques known as autogenic training. Autogenic training is a well-known method in Europe for the treatment of anxiety and stress disorders. The practice of autogenic training is also reported to improve neurovegetative and immune regulation. This study focuses on describing how autogenic training is helping its practitioners to cope with the pandemic. Specifically, they report strong beneficial effects on their physical, psychological, and relational health. In total, 75 autogenic training practitioners (41 women), age 22–71, participated in the survey. An ad-hoc questionnaire was developed to collect information on sociodemographic variables, health status during the pandemic, characteristics of their AT practice, and response to the pandemic as outcome variables. The questionnaire was distributed through Google Forms in the first week of September 2020. The results show that there was an increase in the practice of autogenic therapy during the pandemic, especially among women. In addition, the majority of participants (88%) remained healthy during the pandemic. Furthermore, the results show that autogenic training is very useful for physical and psychological health and for a better understanding of others. Therefore, the practice of autogenic training is recommended to people who live moments of anxiety, are afraid of illness, or feel that they have to improve the quality of relationships with others.